PENGARUH KEPEMIMPINAN MANAJEMEN SEKOLAH DAN PROFESIONALISME GURU TERHADAP KINERJA GURU SMK WACHID HASYIM 2 SURABAYA - Andini Zahra Adystia; Nugroho Mardi Wibowo (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
This study aims to determine and analyze the influence of school management leadership and teacher professionalism on teacher performance at SMK Wachid Hasyim 2 Surabaya. A quantitative approach was used in this study with a population of 34 people and using a saturated sample so that the entire population became research respondents. The results of the study show that simultaneously, school management leadership and teacher professionalism have a significant influence on teacher performance. Partially, school management leadership and teacher professionalism have a significant influence on teacher performance, and teacher professionalism has a dominant influence on teacher performance.